Effect of Piriformospora indica inoculation on some morphophysiological traits of fenugreek under cadmium stress - fatemeh sakhai; zahra movahedi; mehdi ghabooli; ehsan mohseni fard (علوم و فناوری بذر ایران)
Heavy metal stress is one of the most important factors limiting the growth and yield of plants in many parts of the world. The fungus Piriformospora indica, as a mycorrhizal endophytic fungus, stimulates the growth of many plant species and also increases the resistance to biotic and abiotic stress. In this research, the interaction effect of P. indica and Cd on germination of fenugreek, also the interaction effect of P. indica and Cd in soil system were investigated on morphophysiological traits of fenugreek according to a factorial experiment based on completely randomize design (CRD) with 3 replication in two independent experiments. The results of interaction effect of P. indica and Cd on germination of fenugreek showed that Cd stress may give to plants allows germination, but increased in their concentration impaired the some seed germination indices of fenugreek. Also the results of the interaction effect of P. indica and Cd in soil culture showed that Cd stress reduced the most of measured morphological traits mean and increased the most of enzyme studied in fenugreek. According to these results, it seems that the fungus in addition to colonization of fenugreek also has an effect on its improvement in Cd stress.